Modelling of Facility Layout Improvement and Breakeven Point Forecast for Plantain Flour Production - Adeyeri, Michael Kanisuru; Ayodeji, Sesan Peter; Adeleye, Adebanji (International Journal of Integrated Engineering, 2021)
: A plantain flour process plant consisting of washing, grating, drying, milling and sieving machines could be set up in a single static layout pattern. But for greater productivity, more efficient use of facility, reduction in processing time and elimination of bottlenecks along the process plant could be obtained. An improved facility layout model was developed for a plantain flour process plant using data from an existing process plant by considering: the breakeven point for investment; and reliability of the facility layout. Comparison was made using data from the initial layout pattern (static layout) with the dynamic layout pattern to aid robust modelling. Considerable level of reduction in the cost of material handling was achieved as congestion along the process plant was minimized and processing time in the dynamic layout generated was much reduced. The breakeven analysis result reflects the extent of improvement per throughput. Testing the models with throughput sizes of 21.87 kg, 43.74 kg, 65.62 kg, 87.49 kg and 109.36 kg, the average processing time to breakeven point was 4703.9 minutes, and this was drastically reduced by 36 % to an average of 3008.5 minutes when the improved facility layout model was introduced.